Are Nasopharyngeal Cultures Useful in Diagnosis of Acute Bacterial Sinusitis in Children?. (December 2013) - Shaikh, Nader; Hoberman, Alejandro; Colborn, D. Kathleen; Kearney, Diana H.; Jeong, Jong H.; Kurs-Lasky, Marcia; Barbadora, Karen A.; Bowen, A'Delbert; Flom, Lynda L.; Wald, Ellen R.
The diagnosis of acute bacterial sinusitis can be challenging because symptoms of acute sinusitis and an upper respiratory tract infection (URI) overlap. A rapid test, if accurate in differentiating sinusitis from URI, could be helpful in the diagnostic process. We examined the utility of nasopharyngeal cultures in identifying the subgroup of children with a clinical diagnosis of acute sinusitis who are least likely to benefit from antimicrobial therapy (those with completely normal sinus radiographs). Nasopharyngeal swabs were collected from 204 children meeting a priori clinical criteria for acute sinusitis. All children had sinus X-rays at the time of diagnosis. To determine if negative nasopharyngeal culture results could reliably identify the subgroup of children with normal radiographs, we calculated negative predictive values and negative likelihood ratios. Absence of pathogens in the nasopharynx was not helpful in identifying this low-risk subgroup.